Type 2 Diabetes, Obesity, and Breast Cancer Risk: The Multiethnic Cohort - Maskarinec, Gertraud (Cancer Epidemiol Biomarkers Prev, 2017)
BACKGROUND: Obesity has been more consistently associated with breast cancer than type 2 diabetes (T2D). This analysis examined the combination of the two factors in the Multiethnic Cohort (MEC). METHODS: Women aged 45-75 years entered the MEC in 1993-1996 by completing a questionnaire. T2D status was self-reported at baseline, two follow-up questionnaires, and confirmed by administrative data. Cancers were identified from tumor registries and deaths through vital records until 2010. Cox regression was applied to estimate hazard ratios (HR) and 95% confidence intervals (CI) for BMI and T2D status alone and in combination. RESULTS: Among 103,721 (25,146 white, 20,255 African American, 7,681 Native Hawaiian, 28,012 Japanese American, 22,627 Latina) women with 14,558 T2D cases, 6,692 women developed breast cancer during 14.8±4.1 years of follow-up. T2D was significantly associated with breast cancer risk (HR, 1.15; 95%CI, 1.07-1.23), but including body mass index (BMI) lowered the HR to 1.08 (95%CI, 1.00-1.16). Ethnic-specific BMI-adjusted models showed elevated risks for T2D in Latinas only (HR, 1.30; 95%CI, 1.11-1.52). In contrast, obesity predicted statistically significant 21%-46% higher risks, after T2D adjustment, in all ethnic groups except Latinas (HR, 1.17; 95%CI, 0.99-1.38). CONCLUSIONS: As reported previously, inclusion of BMI weakened the association of T2D with breast cancer. T2D status but not BMI was primarily associated with higher breast cancer risk in Latinas. IMPACT: The role of obesity and T2D in breast cancer etiology may differ by ethnicity suggesting metabolic differences related to obesity.